Optimization of an innovative hybrid thermal energy storage with phase change material (PCM) wall insulator utilizing Taguchi method - Kurnia, J.C. (Elsevier Ltd, 2022)
Most studies considered low conductivity of phase change material as negative point on its application in hybrid thermal storage. However, it has hidden potential to be used as an effective insulation for thermal storage while at the same time acts as energy storage medium. Based on our literature survey, no previous study investigating this configuration has been reported. This experimental study are thus conducted to evaluate the energy storage performance of the Hybrid TES with PCM layer as insulation wall and energy storage, and to assess the effect of several key geometry and operating parameters on the performance of the Hybrid TES. To achieve these objectives, an experimental setup consisting of hybrid TES tank with PCM embedded in the wall and flow loop for heat transfer fluid is prepared. Insulation tests are carried out to evaluate its PCM wall insulation effectiveness. During charging and discharging cycle, k-type thermocouples connected with datalogger are utilized to measure and record the temperature profile of the working fluid and PCM layer with TES. Three important parameters of the proposed Hybrid TES including the ratio of PCM volume to heat transfer fluid (HTF) volume, inlet temperature and volumetric flow rate of the HTF, are studied to evaluate their influence on the Hybrid TES performance. Taguchi statistical method is adopted to minimize the number of experiments whilst securing all important information and parameter interaction. Based on the experimental results, it was found that Hybrid TES with PCM wall layer offers better insulation, indicated by higher retained temperature within the storage, than its conventional sensible TES counterpart. In addition, TES heat storing capacity is increased by introducing the PCM wall. Among the investigated parameters, HTF inlet temperature has the most significant positive effect on the performance of Hybrid TES. This study signifies the potential of PCM wall incorporation into TES as wall insulation and additional thermal energy storage medium. Â© 2022